Pengaruh Model Pembelajaran Inkuiri Terbimbing Pada Pembelajaran Kimia Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIA SMAN 7 Mataram Tahun 2019 - Abdurrahman, Hary; Wildan, Wildan; Loka, I Nyoman (Jurnal Ilmiah Pendidikan Indonesia, 2020)
This research aims to investigate the effect guided inquiry learning model on chemistry learning towards critical thinking skills students at class XI MIA SMAN 7 Mataram 2019. Quasi experimental in the form of non-equvalent control group design is the type of this study. The population of this research was all students of XI MIA SMAN 7 Mataram. Purposive sampling method was chosen to be the sampling method of this study. The sample of this study were XI MIA 3 as the experiment class and XI MIA 4 as control class. In experiment class, guided inquiry learning model Student given, whereas conventional learning model with lecture method was applied in control class. The result of statistic test at significant level (5%) showed that tcount (3,33) > ttable (2,009). The average score of experiment class is 69,72 with the median is 67,6 which is higher than the average score of control class is 62,17 with the median is 58,3. The standart deviation of experiment class is 7,494 which is smaller than the standart deviation score of control class is 8,009 which means the experiment class is more homogeneous than the control class. Based on these results it can be concluded that difference in scores between the two classes did not occur by accident, but because of guided inquiry learning model effect.